Intelligent predictive neural network analysis on two phase bioconvection flow of dusty hybrid nanofluid with Cattaneo Christov flux model and melting phenomena - Raza, Ali; Safra, Imen; Liaqat, Saba; Rakhmonov, Farkhod; Abbas, Munawar; Farkhad, Durdana Rustamova; Darem, Abdulbasit A. (Springer, 2026)
BackgroundThis analysis's main purpose is to investigate the outcome of melting heating on microorganisms in a two-phase bioconvection flow of a dusty hybrid nanofluid via a sheet with Cattaneo-Christov flux model.MethodUsing an appropriate similarity transformation, constitutive partial differential equations are transformed into ordinary differential equations. Using reference datasets from numerical calculations, we train and assess the intelligent Bayesian regularized predictive neural network approach to forecast flow solutions under different physical parameter scenarios.ApplicationsThis model is valuable in advanced thermal and environmental engineering systems that combine two-phase flows, particulate matter, and microorganism-induced bioconvection. It is used in melting and solidification processes, including phase-change materials, metal casting, and thermal energy storage systems, where dusty hybrid nanofluid improve heat transport. The Cattaneo-Christov flux model's addition makes it applicable to high-speed thermal transport and conduction of non-Fourier heat in micro- and nanoscale devices.OutcomesWhen the thermal and solutal relaxation parameters' values rise, the solutal and thermal distribution improves. Histogram analysis, regression analysis, statistic transition, and Mean square error analysis all show that it is accurate when compared to reference data.
Keywords: Dusty Hybrid Nanofluid; Gyrotactic Microbes; Melting Heating; Cattaneo-Christov Flux Model; Artificial Neural Network